Immersive learning platforms: analyzing virtual reality contribution to competence development in higher education—a systematic literature review - Cabrera-Duffaut, Augusto; Pinto-Llorente, Ana María; Iglesias-Rodríguez, Ana (Frontiers in Education, 2024)
Background: This study evaluates the effectiveness and pedagogical integration of Virtual Reality (VR), exploring its application in various educational contexts. In this systematic literature review, the role of virtual reality in enhancing competency development within higher education is examined.The search was conducted in two databases (Scopus and Web of Science) following the PRISMA method guidelines. Inclusion criteria were limited to studies that used virtual reality as a tool within the classroom, analyzing the competencies developed through its application.Results: Out of the 1671 articles retrieved, 61 full texts were selected for review, resulting in 27 academic articles published in the last five years. The findings highlight the capacity of virtual reality to foster interpersonal skills while simultaneously addressing the challenges of its integration. Discussion: The adoption of Virtual Reality (VR) in higher education is notable for its immersive learning experiences. Despite VR's significant contribution to education, its widespread integration faces challenges, including the high costs of VR technology and the lack of specialized educational software, which limits its accessibility across various academic disciplines.The advent of global technological advancements has unveiled numerous opportunities within the educational sector, with VR emerging as a transformative technology that offers immersive learning experiences, propelling educational methodologies beyond traditional boundaries. Through this SLR, it becomes evident that the application of VR in education transcends mere knowledge transfer, facilitating the development of critical competencies.